Analisis Penerapan Smart Qris Menggunakan Framework ITIL V3 Pada Pasar Tradisional Baturaja - Beni Ariansyah; Nadya Kusuma Wardhani; Ninna Mugianti Utami; Tata Sutabri (Economics and Digital Business Review, 2023)
The problems that have an impact in implementing QRIS are less than optimal, namely: (1) Lack of merchant education when making transactions in their stores so that the delivery of QRIS use must be clear. (2) Scanning of QRIS codes cannot be done by consumers. (3) Lack of precise pasting on the QRIS sticker cashier desk. Many discoveries in sticker payment applications are more than one QRIS. qualitative descriptive. Qualitative research is an understanding of the interactive process in the scientific community in improving and approaching the phenomenon under study (Aspers &; Corte, 2019). Data collection techniques based on Bank Indonesia regulations from this researcher are analyzing interviews, documentation to complement research on payment systems and observations. The stages of data collection are carried out directly in the preparation of research instruments, research subjects, research techniques, data collection, data fulfillment analysis stages and reporting the results studied. The conclusion of this study can be elaborated, namely, merchants using Quick Response Code IndonesiaStandard (QRIS) in the Baturaja Traditional Market throughout 2020 increased by 201.3% in a year. This matter is intertwined because of the policy in mandatory QRIS consumption starting January 1, 2020 and the formation of the Covid-19 pandemic which has made people reduce the use of cash.